Moses Samuel Lowe - Engraver, Draughtsman and Miniature Painter of German (Jewish) Enlightenment. - Lohmann, Uta (Naharaim -- Journal of German -- Jewish Literature & Cultural History / Zeitschrift für Deutsch -- jüdische Literatur und Kulturgeschichte, 2026)
The engraver, draughtsman, and miniature painter Moses Samuel Lowe (1756–1831) is almost forgotten today. This essay searches for traces of his life and his artistic work. Lowe's work in the educated circles of Berlin is particularly explored. As one of the first Jewish artists to receive an academic education, Lowe was characterized by tireless creativity and inventiveness. He gained his artistic experience mainly within the sociable networks of the Berlin Enlightenment and the Prussian Haskalah, to which he remained ideologically and conceptually connected throughout his life. His portraits gave individual faces to many of the thinkers in these scholarly and literary circles. Lowe also provided illustrations for their publications, which, with their often allegorical expressiveness, served the vivid cognition of the recipients and thus contributed significantly to the educational intention of the writings.